2016
DOI: 10.12700/aph.13.5.2016.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Impact Assessment on the Success of Strategic Investment Projects: Benchmarking Among Different Sector Companies

Abstract: The paper explores the impact of the main elements of the strategic investment projects management process in South East

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…2001 and. Furthermore, success and failure rates may vary depending on the type of project, such as industry type, complexity, client, size, and uniqueness (Ojiako, Johansen, and Greenwood 2008). According to Amade et al (2012).…”
Section: Risk Monitoring and Controlmentioning
confidence: 99%
“…2001 and. Furthermore, success and failure rates may vary depending on the type of project, such as industry type, complexity, client, size, and uniqueness (Ojiako, Johansen, and Greenwood 2008). According to Amade et al (2012).…”
Section: Risk Monitoring and Controlmentioning
confidence: 99%
“…Researchers have also highlighted that not only should the success rate be identified, and the success criteria based on which the success rate is defined, but also the factors that increase the potential for achieving success [10,31,[53][54][55]. Moreover, Müller and Turner [56,57] revealed that project managers play a key role in achieving project success since they can compensate for minor deficiencies; Goleman [58] highlighted the need for a proper, empathy-based leadership style; Fekete and Szontágh [29] and Jovanović et al [59] identified how risk management bears critical importance; Abdi Khalife and coauthors [1] argued that project management can increase efficiency and effectiveness; and Wang et al [60] noted that, in addition to adequate resource availability and public support, stakeholder management, communication, and a clear strategic vision are invaluable for achieving project success. However, researchers have also highlighted the need for a strong business case [61,62].…”
Section: Project Successmentioning
confidence: 99%